Model review and algorithm comparison on multi-objective disassembly line balancing - Laili, Yuanjun; Li, Yulin; Fang, Yilin; Pham, Duc Truong; Zhang, Lin (Journal of manufacturing systems, 2020)
•The mathematical models of disassembly line balancing are summarised.•The transformations between different disassembly line balancing models are discussed.•Seven multi-objective evolutionary algorithms are compared for solving different disassembly line balancing problems.•The experimental results can be a baseline for further research on multi-objective disassembly line balancing. As the disassembly of end-of-life products is affected by several dynamic and uncertain issues, many mathematical models and solution approaches have been established. However, with more extended objectives, constraints and different methods of disassembly, inconsistent models relating to product representations and types of disassembly lines have become the main barriers for the transfer of research to practise. In this paper, a systematic overview of recent models to summarise the input data, parameters, decision variables, constraints and objectives of disassembly line balancing are presented. After discussing the adaptation and extensibility of these models for different environments, a unified encoding scheme is designed to apply typical multi-objective evolutionary algorithms on this problem with extensive decision variables and seven significant objectives. Algorithm comparison on four typical cases is then carried out based on seven commonly used products to verify the optimisation process for the integrated version of existing models and demonstrate the overall performance of the typical multi-objective evolutionary algorithms on this problem. Experimental results can be a baseline for further algorithm design and practical algorithm selection on these disassembly line balancing scenarios.